(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Low birth weight (LBW) is an index of our status of public health, maternal health and nutrition. LBW is a multi-factorial problem. The major challenge in the field of public health is to identify the factors influencing LBW and to institute remedial measures. Objective: To find out the maternal risk factors of low birth weight neonates. Materials and Methods: A descriptive cross sectional study was conducted at Combined Military Hospital (CMH), Ghatail from January 2018 to June 2019. A total of 707 mothers were included in this study who delivered live infants during study period; among them, 122 were LBW neonates. All the mothers of LBW neonates were evaluated and data were collected by using structured questionnaire. Results: A total 707 live birth occurred during the study period of which 122 were LBW and the incidence of LBW was 17.3%. Out of 122 mothers 18(14.8%) were <20 years, 69 (56.6%) were between 20-30 years and 35(28.7%) were >30 years of age; 19(15.6%) were underweight, 83 (68.0%) were normal weight and 20(16.4%) were overweight and obese; 34(27.9%) took inadequate antenatal check up and 88(72.1%) mother took adequate antenatal check up. Among 122 mothers 25(20.5%) were para 01, 47(38.5%) were para 02 and 50(41%) were para ≥ 03; 16(13.1%) had birth space <2 years and 106(86.9%) had birth space >2 years; 09(7.4%) educated upto primary school, 73(59.8%) educated upto high school and 40(32.8%) educated upto college & above. Regarding maternal illness 30(24.6%) mothers had premature rupture of membranes (PROM), 20(16.4%) had hypertension (HTN), 12(9.8%) had diabetes mellitus (DM), 05(4.1%) had severe oligohydramnios, 05(4.1%) had chronic anaemia and 06 had other illness (4.9%). Conclusion: The risk factors for LBW babies identified in this study are modifiable. In order to reduce this menace, holistic approaches such as health education, maternal nutrition and increasing the quality and quantity of the antenatal care services are of paramount importance. JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 55-58